NEW PLAYERS IN ALTERED TOLERANCE TO THYROID GLAND ANTIGENS: AN IMMUNOPATHOGENESIS CONCEPT OF AUTOIMMUNE THYROID DISEASE (REVIEW) - V. V. Zdor (SPb RAACI, 2016)
Precise mechanisms of tolerance loss to thyroid auto-antigens are still largely unknown, thus preventing further elucidation of key pathogenetic stages in autoimmune diseases affecting thyroid gland, and, therefore, to identify target pathways for treatment of these disorders. Detailed studies on the role of innate and adaptive immune cells in disturbed tolerance to autoantigens specific for thyroid gland in Graves’ disease and autoimmune Hashimoto’s thyroiditis have revealed and provided a number of theoretical foundations for arrangement of clinical immunological monitoring and forecasting of these diseases in a long-term prospective.